2019
DOI: 10.3390/en12040649
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Prioritization of Risk Factors in an Electrical Generator Based on the Hybrid FMEA Framework

Abstract: The oil and gas industry is looking for ways to accurately identify and prioritize the failure modes (FMs) of the equipment. Failure mode and effect analysis (FMEA) is the most important tool used in the maintenance approach for the prevention of malfunctioning of the equipment. Current developments in the FMEA technique are mainly focused on addressing the drawbacks of the conventional risk priority number calculations, but the group effects and interrelationships of FMs on other measurements are neglected. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…The results obtained showed that multiple factors always influenced the accidents′ occurrence, confirming the need to take into account the interactions between the different aspects that characterize working operations. This is consistent with the research cues coming also from other fields, such as the agriculture [84] or the oil and gas sectors [85], confirming that the interdependencies among the different variables of an accident should be scrutinized as in most cases the determinants of a fatality are multiple and interconnected, overlapping with each other [36]. As far as the electrical accidents are concerned, the results show that most fatalities occurred to workers carrying out activities not related to specific electrical works (cluster 2).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results obtained showed that multiple factors always influenced the accidents′ occurrence, confirming the need to take into account the interactions between the different aspects that characterize working operations. This is consistent with the research cues coming also from other fields, such as the agriculture [84] or the oil and gas sectors [85], confirming that the interdependencies among the different variables of an accident should be scrutinized as in most cases the determinants of a fatality are multiple and interconnected, overlapping with each other [36]. As far as the electrical accidents are concerned, the results show that most fatalities occurred to workers carrying out activities not related to specific electrical works (cluster 2).…”
Section: Discussionsupporting
confidence: 91%
“…As far as the electrical accidents are concerned, the results show that most fatalities occurred to workers carrying out activities not related to specific electrical works (cluster 2). On the one hand, such an output is in line with the results of similar studies in other countries [75,85], highlighting the high rate of electrical accidents among construction workers different from electricians. On the other hand, this aspect fosters the need of a more accurate and multidisciplinary training of both workers and safety managers.…”
Section: Discussionsupporting
confidence: 89%
“…However, profits grow immediately after program implementation, which can be drawn out only for some equipment or if the equipment is nonstandard [10]. Several studies have reported the drawbacks, as follows [11][12][13][14][15][16]: complicated, time-consuming, costly, too qualitative an approach, shortfalls in safety due to a failure to update maintenance approaches, a lack of identification and prioritization for failure modes, and handling each failure mode individually, which misses out on the combinational effects of failure modes.…”
Section: Introductionmentioning
confidence: 99%
“…The practical application to the typical failure modes of the propulsion subsystem is provided. The assessment results show that this system contributes to risk priority decision-making and disastrous accident prevention.The so-called risk priority number (RPN) technique is employed to assess the risk levels of known or potential failure modes in traditional FMEA, defined as the product of the probability of severity (S), occurrence (O), and detectability (D) [9,10]. According to the priority ranking of failure modes, preventive and compensatory actions are introduced for the key equipment.…”
mentioning
confidence: 99%
“…The so-called risk priority number (RPN) technique is employed to assess the risk levels of known or potential failure modes in traditional FMEA, defined as the product of the probability of severity (S), occurrence (O), and detectability (D) [9,10]. According to the priority ranking of failure modes, preventive and compensatory actions are introduced for the key equipment.…”
mentioning
confidence: 99%